2000
DOI: 10.1128/jvi.74.3.1383-1392.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Panel of Insertion Mutants in Human Cytomegalovirus Glycoprotein B

Abstract: Glycoprotein B (gB; gpUL55) of human cytomegalovirus (HCMV) plays a critical role in virus entry and cell-to-cell spread of infection. To define the structure-function relationships in gB, a panel of linker-insertion mutations was generated throughout the coding region. This strategy yielded a panel of 22 mutants with four amino acid insertions and 3 large truncation mutants. Assessment of the mutant proteins' biosynthetic properties and folding patterns analyzed in context with predicted secondary features re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
(60 reference statements)
3
19
0
Order By: Relevance
“…Similar findings have been reported by Singh et al, who described linker insertion mutants of gB with mutations outside of AD-1 that lead to loss of oligomerization and cleavage (44). Interestingly, these investigators also noted that a linker insertion mutant within AD-1 (aa 627) leads to loss of reactivity by an AD-1-specific MAb and loss of oligomer formation (44). This finding independently demonstrated that AD-1 formation was required for oligomer formation and transport of gB from the ER.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings have been reported by Singh et al, who described linker insertion mutants of gB with mutations outside of AD-1 that lead to loss of oligomerization and cleavage (44). Interestingly, these investigators also noted that a linker insertion mutant within AD-1 (aa 627) leads to loss of reactivity by an AD-1-specific MAb and loss of oligomer formation (44). This finding independently demonstrated that AD-1 formation was required for oligomer formation and transport of gB from the ER.…”
Section: Discussionsupporting
confidence: 89%
“…We would argue that the gB Cys mutations at positions 508 and 550 resulted in misfolded molecules that failed to exit the ER and did not oligomerize, based on their lack of reactivity with MAb 27-39. Similar findings have been reported by Singh et al, who described linker insertion mutants of gB with mutations outside of AD-1 that lead to loss of oligomerization and cleavage (44). Interestingly, these investigators also noted that a linker insertion mutant within AD-1 (aa 627) leads to loss of reactivity by an AD-1-specific MAb and loss of oligomer formation (44).…”
Section: Discussionsupporting
confidence: 79%
“…The more global approach of linker-insertion mutagenesis was used with HSV-1 gB (5,24,29) and with HCMV gB (36). For the HCMV protein, several mutants that retained correct folding were identified, but no functional assay was available to test their activity (36).…”
Section: Fig 2 Quantitation Of Virus Entry (Complementation)mentioning
confidence: 99%
“…For the HCMV protein, several mutants that retained correct folding were identified, but no functional assay was available to test their activity (36). For the HSV-1 protein, all mutants except one either retained functional activity or were misfolded, so only one candidate functional domain was identified.…”
Section: Fig 2 Quantitation Of Virus Entry (Complementation)mentioning
confidence: 99%
“…An in-frame, four-amino-acid insertion mutant six amino acids downstream of C250 (mutant I-256) resulted in the loss of recognition by monoclonal antibody 27-39, which recognizes a folded and conformation specific epitope, indicating that this region may be important in the final folded form of gB (28). The I-256 insertion mutant also showed a defect in proteolytic processing by furin despite the fact that the furin cleavage site is over 200 amino acids downstream of the insertion.…”
mentioning
confidence: 99%